Navigating Strategic Security Landscape in the Black Sea: A Multi-Theoretical Analysis and Prospective Scenarios - Dr. Assad Mehmood Khan (Review Journal of Social Psychology & Social Works, 2025)
The Black Sea region serves as a critical arena for geopolitical competition, with far-reaching implications for regional stability and global security. Understanding the complexities of its strategic security landscape is imperative for formulating effective policies and strategies to address emerging challenges. Considering this hypothesis, the purpose of this research focused on analyzing the motives and actions of major stakeholders, including Russia, the United States, and other regional players, and assesses their impact on the security landscape. Additionally, the study forecasts prospective scenarios to anticipate future developments and their implications. The study adopts a multi-theoretical method, integrating insights from Realism, Liberalism, Constructivism, and Game Theory to analyze the strategic security landscape of the Black Sea. Data analysis employs various Game Theory models, including Stag Hunt and Prisoners' Dilemma, to elucidate strategic interactions among actors in the region. Prospective scenarios are forecasted using Dominant Strategy analysis. Results underscore the complex interplay of interests and the potential for heightened security risks in the Black Sea region. The study provides valuable insights for policymakers, analysts, and stakeholders to develop strategies to address emerging security challenges and foster regional stability.